Epigastric hernia: 150 cases - Croci, Fabio; Gastambide, Carmelo; Pérez Penco, Ernesto; Cordal, Adriana (Cirugía del Uruguay, 1984)
Authors study the clinical and anatomo-pathological characteristics, as well as the surgical procedure and its results, in a series of 150 epigastric hernias, with a mínimum three-years follow up. lts predominance in males and the high frequency of associated parietal pathology is pointed out. There are thus far a 4% of verified recidivation. No conclusions could be drawn in respect of the effectiveness of transversal repair of same.